Discovery of Plastics-degrading Enzymes - Mehmet Mervan Çakar; Marija Vuković Domanovac; Zvjezdana Findrik Blažević (Kemija u Industriji, 2023)
Plastics are highly advanced materials that have a vast array of applications and are produced globally in an approximate amount of 350 to 400 million tons every year. Nevertheless, there are serious concerns about plastic waste and pollution as a result of the misuse and lack of control of their use in industries, including packaging, transportation, manufacturing, and agriculture. Approximately 1,000 years are required for plastic bags to decompose efficiently. Additionally, CO2 and dioxins are released into the atmosphere by burning plastics, and they contribute to global warming. The Earth’s environment is overwhelmed with waste, mostly from poor recycling practices and low circular usage, resulting in millions of tons of waste generated annually. To combat this, new technologies for recycling post-consumer plastics are desperately needed to decrease plastic waste and improve the environment, while also finding ways to utilise these materials. Due to the inadequate disposal methods currently available for plastic waste, there has been increased interest in the use of microorganisms and enzymes designed for the biodegradation of non-degradable synthetic polymers via biocatalytic depolymerisation indicating that plastics treatment and recycling can be more efficient and sustainable.